Guided ultrasonic waves propagation imaging: a review - Chen, Ciang Chia; Shi, Yn Lee; Harmin, Mohammad Yazdi; Yunshil, Choi; Lee, Jung-Ryul (Institute of Physics Publishing, 2023)
This article presents a comprehensive review of the laser-based guided ultrasonic waves propagation imaging (G-UPI) system and respective signal/data processing methods related to the nondestructive testing and evaluation of thin-walled structures. The primary goal of this study is to review and recognize various processing methods, explain the working principles of the most influential methods, and highlight outstanding capabilities. In addition, the suitability of the methods for multiple types of damage and defect in various materials and structures are presented. At the same time, success stories of difficult-to-inspect cases are highlighted. Its secondary goal is to compare and discuss the merits and demerits of the laser-scanning part of the system for ultrasound generation and acquisition to provide a guideline for scanning scheme or hardware selection. Finally, the potential challenges and prospects of the G-UPI are discussed. It is expected that this review would serve as an entrance key for newcomers and a reference point for researchers to explore the opportunities for further improvement in the laser ultrasound-based evaluation of critical engineering structures.